Persistent Tachycardia in a Patient on Clozapine. (7th July 2020) - Adeyemo, Samuel; Jegede, Oluwole; Rabel, Peterson; Ahmed, Saad; Tumenta, Terence; Oladeji, Oluwatoyin; Taher, Khanderker
Abstract : Tachycardia emergent from clozapine treatment is usually transient, often missed, unreported, and therefore frequently goes untreated resulting in possible premature discontinuation of an otherwise effective treatment. Clozapine-induced tachycardia results from direct effects on the sympathetic nervous system including the blockade of cardiac muscarinic M2 receptors, presynaptic α 2 adrenoceptors, and indirect activation of the β adrenoceptors. Unfortunately, there are no clear guidelines for monitoring or treating tachycardia induced by clozapine. We present a case of a 55-year-old man with treatment-resistant schizophrenia initiated on clozapine who developed persistent tachycardia and right bundle branch block in the course of treatment. Tachycardia persisted despite treatment with metoprolol and necessitated a transfer to the intensive care unit. A reduction in clozapine dose with the addition of adjunctive antipsychotic(lurasidone) stabilized the patient's heart rate. This case highlights the need for consistent physical examination and a multidisciplinary-based treatment approach for patients on clozapine. The case also suggests that clozapine dose reduction and combination antipsychotic treatments may preclude the need to discontinue clozapine in patients with persistent tachycardia.